2014
DOI: 10.3945/jn.113.188789
|View full text |Cite
|
Sign up to set email alerts
|

Folate and Cobalamin Modify Associations between S-adenosylmethionine and Methylated Arsenic Metabolites in Arsenic-Exposed Bangladeshi Adults

Abstract: Chronic exposure to inorganic arsenic (InAs) through drinking water is a major problem worldwide. InAs undergoes hepatic methylation to form mono- and dimethyl arsenical species (MMA and DMA, respectively), facilitating arsenic elimination. Both reactions are catalyzed by arsenic (+3 oxidation state) methyltransferase (AS3MT) using S-adenosylmethionine (SAM) as the methyl donor, yielding the methylated product and S-adenosylhomocysteine (SAH), a potent product-inhibitor of AS3MT. SAM biosynthesis depends on fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 50 publications
2
42
1
Order By: Relevance
“…This lack of association with PC2 was not evident when examining the association of water arsenic with PMI, iAs%, or MMA% (presumably because these phenotypes are correlated with DMA% and PC1). Previous studies suggest that the second methylation step is inhibited at increased exposure levels (particularly elevated levels of iAs III and MMA III ) both in the experimental setting (63,64) and in human observational studies (65), consistent with the associations observed in this study.…”
Section: Discussionsupporting
confidence: 91%
“…This lack of association with PC2 was not evident when examining the association of water arsenic with PMI, iAs%, or MMA% (presumably because these phenotypes are correlated with DMA% and PC1). Previous studies suggest that the second methylation step is inhibited at increased exposure levels (particularly elevated levels of iAs III and MMA III ) both in the experimental setting (63,64) and in human observational studies (65), consistent with the associations observed in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Arsenic is methylated in the body by methyltransferases, including As methyltransferase (AS3MT), with SAM as main methyl donor (Marafante 1984). Folate plays an important role in one-carbon metabolism by recruiting methyl groups and is associated with individual variation in arsenic methylation capacity (Howe, Niedzwiecki et al 2014). Although we did not measure folate status, low dietary folate intake (<300 and 200 µg/d) was observed in 15% and 4% of the study children, respectively, suggesting that deficiency is not prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…As noted previously (Section 3.2.1), methylation of iAs requires the conversion of S-adenosylmethionine (SAM) to S-adenosylhomocysteine (Howe et al, 2014), which eventually becomes homocysteine (Gamble et al, 2005;States et al, 2009;Zakharyan and Aposhian, 1999). Efficient metabolism of homocysteine requires adequate intake of vitamin B6, B12 and folic acid; thus, considering the findings of Chen et al (2007a), iAs may exert its effect on CVD through the formation of homocysteine, particularly in individuals with insufficient levels of folate and B vitamins .…”
Section: Epidemiology Of Inorganic Arsenic and Cvdmentioning
confidence: 95%